Evaluation of Biochemical and Haematological Responses of Common Carp (Labeo rohita) after treatment with medicinal herb Curcuma cassia - Mallik, Ahmed Reyaz; Shammi, Qaiser Jehan; Telang, Sanjay (Journal of Drug Delivery and Therapeutics, 2019)
Curcumas are the unimaginable world of hidden gingers, which get its name from some of the varieties because they bear their flowers on short stalks amid its foliage. Curcuma cassia is a perennial monocot herb with fleshy rhizomes. The present study deals with the use of medicinal plant Curcuma cassia in fish diet to study the biochemical and haematological profile on Labeo rohita a common fish. The plant was extracted and processed for decoction method. The extract obtained was then mixed with 0.5 kg salt (NaCl) and 1.0 kg fish feed powder in the ratio 10:1. Required amount of sterilized water was mixed to make it paste. Haematological and biochemical studies were done after administering the extracts for 30days. Based on the results it is appropriate to conclude that the plant extract of Curcuma cassia incorporated in fish diet may improve the biochemical and haematological profile in blood of fish Labeo rohita. It was observed that the herbal diet fed fishes exhibited significant increase in RBC, WBC, serum protein and globulin and also maintained hepatics disorder enzymes (ALT, AST, ALP) which may be considered as a sign of improvement in health status. It may be due to the presence active components i.e. carbohydrates, proteins, glycosides, alkaloids, flavonoids. Phytochemicals in herbs may act as a potent gradient in improving the health of fishes as well as human beings. Keywords: Labeo rohita, Curcuma cassia, Biochemical, Haematological profile, Fish